Respuesta :

To solve this, the problem is solvable by elimination. So you see how the 5y and -5y cancel out? You basically add those two and you add the -7x and 4x and 10 and -10 leaving you with -3x=0. Dividing by each side gives you x=0. Then, plug 0 in for x in -7x+5y=10. Giving you

-7(0)+5y=10.

0+5y=10

5y=10
Divide by 5 on each side giving you y=2. So your answer is (0,2).
Ver imagen ozieltijerina

-7x+5y=10

4x-5y=-10

Find x first by eliminating the y.

Add the two equations together.

-7x+4y=-3y

+5y-+5y= 5y-5y=0

10-+10=0

-3x=0

divide both sides by -3

-3x/-3=0/-3

x=0

Find y by using x=0 into -7x+5y=10 ( using substitution  method)

-7(0)+5y=10

0+5y=10

5y=10

divide both sides by 5

5y/5=10/5

y=2

Answer:

(0,2)